O cotidiano da mãe-acompanhante de criança com doença crônica - Teles, Érika Nunes (2009)
This present work had as purpose to investigate like the companion- mother organizes her routine inside and outside the hospital during her child admission. It was realized an investigation starting from a systemic referencial looking for to investigate the organization of the accompanion- mother's routine under integrative focus contemplating the environmental , social and psychological aspects in a public hospital of the municipal district of São Paulo. Three married mothers who had been accompanying their sons during the first intermission period in this hospital about 15 or 45 days participated this investigation. To the data collection a semi- structured interview was used focusing three axes: routine, instructions about her performance during the intermission and hospital rules, positive and negative aspects related to her presence together to her interned son identified for the mother. The data collection was accomplished in the hospital wards. From the analysis of the results it was possible to identify that: a) the mothers noticed and expressed in the interview about the changes provoked in their daily routine as abandonment of the work, of the domestic activities and familiar living starting from the admission; b) the subjects focused as positive aspect the participation in humanization programs offered by the hospital, as well as the psychology section and of the medical team work; c) as negative aspects were identified feelings of solitude and anguish during the internment. The data pointed for the psychologist's work relevance as space reserved for reception and opportunity to express feelings, doubts and hopes. Suggestions are presented for future researches and the relevance of studies of this population